2007
DOI: 10.1007/s00417-007-0582-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of polypoidal choroidal vasculopathy after photodynamic therapy with verteporfin

Abstract: The eyes with PCV, which had been treated successfully with PDT, may have developed new or recurrent PCV during long-term follow-up. Periodical ICGA would be needed to detect abnormal choroidal vascular changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…In contrast to these reports, Sayanagi et al 16 describe three cases of PCV treated with PDT that were followed-up for more than 4 years and report reactivation of a polyp and emergence of a new polyp in all three eyes. The recurrence in the fi rst patient was 15 months after the sixth PDT, in the second, 30 months after the second PDT, and in the third, 36 months after the fi rst PDT.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast to these reports, Sayanagi et al 16 describe three cases of PCV treated with PDT that were followed-up for more than 4 years and report reactivation of a polyp and emergence of a new polyp in all three eyes. The recurrence in the fi rst patient was 15 months after the sixth PDT, in the second, 30 months after the second PDT, and in the third, 36 months after the fi rst PDT.…”
Section: Discussionmentioning
confidence: 81%
“…Some investigators reported no recurrence of PCV after PDT, 6,9 while others reported a recurrence rate of 5% 10 to 9% 8 within a year. Recently, Sayanagi et al 16 reported the clinical features of three cases of PCV treated with PDT that had been followed-up for more than 4 years; recurrence of the PCV was observed in all three cases during this long-term follow-up.…”
mentioning
confidence: 94%
“…Recent reports have shown a benefi cial effect of PDT on VA in PCV. [3][4][5][6][7][8][9][24][25][26][27][28][29] We also previously reported the results of PDT for PCV at 1 and 2 years after treatment. 6,7 At the 1-year follow-up, preservation or improvement of VA was achieved in 80% of cases and improvement of fundus fi ndings in 69%, though polypoidal lesions recurred in 9% of cases.…”
Section: Discussionmentioning
confidence: 88%
“…Short-term outcomes for PCV after PDT as reported by many study groups indicated that PDT might be beneficial for PCV [24][25][26][27][28]. However, over several years' follow-up study, the VA prognosis may not be the same, and the recurrent or newly developed polypoidal lesions could be observed [9,29]. [14,15], while the latter has been proved to be efficacious not only in stabilization or increase of VA but also in causing regression of the polypoidal lesions [15].…”
Section: Discussionmentioning
confidence: 88%